Pengaruh Pijat Oksitosin Terhadap Kecukupan ASI pada Ibu Menyusui - Septiana, Maria; Sari, Intan; Sapitri, Ana (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2022)
Exclusive breastfeeding for six months worldwide is not in accordance with the recommendations of the World Health Organization (WHO). Mother's Milk (ASI) is a natural nutrient for babies with the most suitable nutritional content for optimal growth. However, some mothers cannot give exclusive breastfeeding because the milk does not come out or only comes out a little. Many problems arise on the first day of breastfeeding such as breast milk does not come out so that the baby does not get adequate milk, one of the efforts to increase the adequacy of breast milk is oxytocin massage. Apart from the benefits of breastfeeding, problems in exclusive breastfeeding are one of the main obstacles, namely milk production that is not smooth. Clinically, drug therapy is given to post partum mothers to facilitate breastfeeding. Unfortunately, this method has a dependency effect on the mother. The purpose of the implementation of this community service is to add insight to the community, especially mothers during productive periods, especially mothers who are breastfeeding their babies so that they better understand the benefits of breast milk and emphasize it more than formula milk which society considers better and produces smarter children when compared to exclusive breastfeeding. The material used in this Community Service is the lecture method and direct practice of implementing oxytocin massage to nursing mothers. Based on the results of a preliminary study conducted by interview method with 10 postpartum mothers, 8 postpartum mothers said their breast milk did not come out smoothly and did not know about oxytocin massage, while 2 postpartum mothers said they had heard of oxytocin massage. This community service aims to analyze the effect of oxytocin massage on the adequacy of breastfeeding in postpartum mothers at BPM Irma Suryadi.Â ABSTRAKPemberian ASI (Air Susu Ibu) eksklusif selama enam bulan di seluruh dunia belum sesuai dengan rekomendasi World Health Organization (WHO). Air Susu Ibu (ASI) merupakan nutrisi alamiah bagi bayi dengan kandungan gizi paling sesuai untuk pertumbuhan optimal. Namun pada sebagian ibu tidak dapat memberikan ASI eksklusif karena alasan ASI tidak keluar atau hanya keluar sedikit. Banyak masalah muncul di hari pertama pemberian ASI seperti ASI tidak keluar sehingga bayi tidak mendapatkan ASI yang memadai, salah satu upaya untuk meningkatkan kecukupan ASI yaitu pijat oksitosin. Terlepas dari manfaat ASI, masalah masalah dalam pemberian ASI eksklusif salah satu kendala utamanya yakni produksi ASI yang tidak lancar. Secara klinis pemberian terapi obat diberikan pada ibu post partum untuk memperlancar ASI. Sayangnya, metode ini memiliki efek ketergantungan pada ibu. Tujuan dari pelaksanaan Pengabdian kepada masyarakat ini adalah untuk menambah wawasan masyakat terutama ibu-ibu masa produktif khususnya ibu yang sedang menyusi bayinya agar lebih memahami manfaat dari Air Susu Ibu dan mementingkannya lebih dari susu formula yang dianggap masyarakat lebih baik dan menghasilkan anak yang lebih pintar bila dibangdingkan dengan ASI ekslusif. Bahan yang digunakan dalam Pengabdian Kepada Masyarakat ini adalah metode ceramah dan praktek langsung pelaksanaan pijat oksitosin kepada ibu-ibu menyusui. Berdasarkan hasil studi pendahuluan yang dilakukan dengan metode wawancara dengan 10 ibu nifas dimana 8 ibu nifas mengatakan ASI nya tidak keluar dengan lancar dan belum mengetahui pijat oksitosin, sedangkan 2 ibu nifas mengatakan sudah pernah mendengar pijat oksitosin. Pengabdian masyarakat ini bertujuan menganalisis pengaruh pijat oksitosin terhadap kecukupan ASI pada ibu nifas di BPM Irma Suryadi.